2006
DOI: 10.1021/pr0602601
|View full text |Cite
|
Sign up to set email alerts
|

Time-Dependent Plasma Protein Changes in Streptozotocin-Induced Diabetic Rats before and after Fungal Polysaccharide Treatments

Abstract: Previous studies about protein modulation with chemically induced models of diabetes in animals have yielded conflicting results, in that many investigators have reported different regulation patterns for the same proteins. Therefore, it is reasonable to determine biomarkers for prognosis and diagnosis of diabetes with time profiling for the candidate proteins. In this regard, we examined the influence of hypoglycemic fungal polysaccharides (EPS) on the time-dependent plasma protein alterations in streptozotoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0
1

Year Published

2008
2008
2012
2012

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 73 publications
1
17
0
1
Order By: Relevance
“…Additionally, it is widely used to induce IDDM in experimental animal models . However, Kim et al (2006aKim et al ( , 2006b reported that fungal EPS might neutralize the ability of STZ to cause -cell damage or induce regeneration of islet -cells. EPS administration after STZ treatment restored serum insulin and glucose levels.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, it is widely used to induce IDDM in experimental animal models . However, Kim et al (2006aKim et al ( , 2006b reported that fungal EPS might neutralize the ability of STZ to cause -cell damage or induce regeneration of islet -cells. EPS administration after STZ treatment restored serum insulin and glucose levels.…”
Section: Discussionmentioning
confidence: 99%
“…previously [13][14][15]. In brief, diabetes was induced by intravenous injection of streptozotocin (50 mg/kg body weight, dissolved in 0.01 M sodium citrate buffer, pH 4.5).…”
Section: January 2009mentioning
confidence: 99%
“…All the animals were randomly divided into three groups with six animals in each group: normal healthy control group (N group), normal rats received 0.9% NaCl solution; STZ-induced diabetic group (STZ group), diabetic rats treated with 0.9% NaCl solution; EPS-treated diabetic group (EPS group), diabetic rats treated with EPS at the level of 200 mg/kg body weight daily for 14 days. The EPS-fed control group was excluded in this study because of similar physiological status to normal control group as described in our previous studies [14,15]. These experiments were approved by the Committee for Laboratory Animal Care and Use, Daegu University.…”
Section: January 2009mentioning
confidence: 99%
See 1 more Smart Citation
“…The extract of P. baumii is known to have various biological activities including inhibition of pulmonary inflammation, antioxidant and free radical scavenging activities [6,7]. In our previous consecutive studies [8][9][10], we have found that the fungal extracellular polysaccharides (EPS) produced by mycelial culture of a medicinal mushroom P. baumii has a strong antidiabetic activity against streptozotocin (STZ)-induced diabetic rats. In addition, it was also observed that the EPS significantly altered and particularly normalized dysregulated plasma proteins in STZ-induced diabetic rats in a time-dependent manner.…”
Section: Introductionmentioning
confidence: 99%